Anti‐Haitianism and Statelessness in the Caribbean. (8th August 2022) - Joseph, Daniel; Louis, Bertin M.
Abstract: Statelessness affects an estimated 15 million people worldwide (Kosinski 2009, 377). Without citizenship in the countries of their birth, stateless people lack access to basic political and social rights, such as the right to vote, marry, travel, and own property; in some cases, stateless people are also denied access to employment, educational services, and health care (UNCHR 2021). In this article, we look at the growing global problem of statelessness through the lens of anti‐Haitianism and ethnographic analysis of people of Haitian descent in the Dominican Republic, Anse‐à‐Pitres, Haïti, and New Providence, Bahamas. [The Bahamas, Dominican Republic, Haiti, the Caribbean, anti‐Haitianism, statelessness] Resumen: La apatridia afecta a unos 15 millones de personas en todo el mundo (Kosinski 2009, 377). Sin ciudadanía en los países de su nacimiento, las personas apátridas carecen de acceso a los derechos políticos y sociales básicos, como el derecho a votar, casarse, viajar y poseer propiedades; en algunos casos, a las personas apátridas también se les niega el acceso al empleo, los servicios educativos y la atención médica (UNCHR 2021). En este artículo, observamos el creciente problema mundial de la apatridia a través de la lente del antihaitianismo y el análisis etnográfico de las personas de ascendencia haitiana en la República Dominicana, Anse‐á‐Pitres, Haití y New Providence, Bahamas. [Las Bahamas, República Dominicana, Haití, el Caribe, antihaitianismo, apatridia]